PENGARUH SENSORY MARKETING: AROMA DAN VISUAL TERHADAP KEPUTUSAN PEMBELIAN - Handoko, Elvina Muliani; Pranata, Sudadi (CV. Denasya Smart Publisher, 2024)
The objective of this research is examining the influence of scent and visual in sensory marketing on buying decision. This research was carried out at Roti'O in Cirebon City. This research forms part of the quantitative method. The data was gained from questionnaire and literature studies. This research used 100 respondents. The results of this research pointed out that scent partially having a positive and not significant influence on buying decision, visual partially having a positive and significant influence on buying decision, and both of the scent and visual simultaneously having a positive and significant influence on buying decision.